Development of Biaung Village Tourism Based on Green Tourism: Pengembangan Desa Wisata Biaung Berbasis Green Tourism - Darmayanti, Putu Widya (Institut Pariwisata dan Bisnis Internasional, 2024)
This study explores the implementation of green tourism in the development of tourism in Biaung Village. The village offers natural and cultural attractions as key tourist draws. Data collection was conducted through observation, in-depth interviews, and documentation. Informants were selected through purposive sampling from individuals knowledgeable about the implementation of green tourism in tourism development. The data were analyzed qualitatively and descriptively. The findings indicate that Biaung Village has applied the concept of green tourism in its tourism development, as reflected in the following facts: (1) Biaung Village preserves nature as a tourist attraction; (2) integrated community empowerment in tourism development has enhanced the vitality of the local economy; (3) cultural and traditional activities of the local community are showcased; and (4) tourists are actively involved in tourism activities to gain new experiences. It is recommended that the development of green tourism-based village tourism raises awareness among the local community to sustainably preserve nature and culture for future generations.